The Central Role of Education in S ocial Problem s and Approaches of Ottom an Intellectuals to Education in the Last Years of the Ottom an Empire - Gündüz, Mustafa (Atatürk Kültür Merkezi Başkanlığı, 2007)
Education has been overrated and it has been seen basic source of modemization in the late Ottoman period. In the early times, education has been considered as a pragmatist but later it has been added an essential character and converter. Mence education gained a vvestem form. The basic character of this is the will of modernization in society. The conflict betvveen tradition and modernization was at highest level in the Second Constitutional Period. The modernization program of the new Republic was mainly discussed and projected in this period. Hence, the impact of the VVestemist, Turkist and Islamist Intellectuals of the Second Constitational Period on the education of the Republic was great. In this article the approaches of the Ottoman intellectuals to education was examined with respect to the similarities of ideas among them.

Eğitim Osmanlı’nın son döneminde oldukça önemsenmiş ve çağdaşlaşmanın temel araçlarından biri olmuştur. Tanzimat’a kadar pragmatist ve geçici bakılan batılılaşmaya sonraları ‘mahiyet katicı’ ve ‘dönüştürücü’ gözle bakılmış ve eğitim batılı bir form kazanmıştır. Bu formun temel karakteristiği kültürel çağdaşlaşmanın sağlanması isteğidir. II. Meşrutiyet, eğitim bakımından gelenek ile modernleşme gayretlerinin en yüksek düzeyde mücadele ettiği am a gelenekselcilerin gün geçtikçe geride kaldığı bir dönemdir. Bu dönemde Cumhuriyet’in çağdaşlaşma programı büyük ölçüde tartışılmış ve projelendirilmiştir. Bu projeler cumhuriyetle birlikte uygulama imkânı bulmuştur. Bu bakımdan cumhuriyet eğitimine II. Meşrutiyet’in batıcı, Türkçü ve İslamcı aydınlarının katkıları büyüktür. Bu yazıda son dönem Osmanlı aydınlarının eğitim düşünceleri özellikle benzer yönleri dikkate alınarak incelenmiştir.
Toplumsal Sorunları Çözmede Eğitime Biçilen Merkezi Rol Ve Son Dönem Osmanlı Aydınlarında Eğitim Düşüncesi